RASKIN DISTRIBUTION IN POVERTY TREATMENT BASED HOUSEHOLD IN 13 ULU SUB-DISTRICT, PALEMBANG CITY - Ahmad Yani Kosali (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2021)
This research was conducted in Kelurahan 13 Ulu Kota Palembang which is relevant to the problems in this study. Researchers collected data by observing, documenting, and interviewing selected informants related to the implementation of the Raskin distribution in household based poverty alleviation. The research design used in this study is a qualitative descriptive study by relying on empirical data and supported by qualitative data. The results of the research conducted indicate (1) basically, the implementation of the Raskin program in Kelurahan 13 Ulu Palembang has run smoothly and is in accordance with the existing general guidelines for the Raskin Program. This can be seen from several aspects of the assessment of the effectiveness assessed from the 6 T, namely the right target beneficiaries, the Raskin distribution that was distributed according to the registered RTS-PMs so that the RTS-PMs were helped in reducing the burden of daily expenses. (2) The key factor for success. The effectiveness of the Raskin program implementation in Kelurahan 13 Ulu cannot be separated from the basic values of management known as